MODEL PEMBELAJARAN LANGSUNG BERBANTUAN MEDIA KONKRET PADA MATERI SUDUT SISWA KELAS IV SDIP BAITUL MAAL - FITRI ANGGRAINI (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2022)
Mathematics is a subject that can build students' abilities and intelligence in problem solving, logical, systematic, analytical, critical, creative and solution thinking. In order that the planned learning objectives of mathematics can be achieved properly through the learning process that takes place in the classroom, the teacher must choose a learning model/method, learning approach/strategy, and appropriate mathematics learning media and adapted to the learning materials and characteristics of students in the classroom. class. In order to achieve learning objectives and assist students in understanding the material about measuring angles, the learning model used to deliver angle material to grade IV SDIP Baitul Maal students is a direct learning model with the help of a concrete model. Direct learning model assisted by concrete media can increase the value of mathematics learning outcomes for fourth grade students of SDIP Baitul Maal Jurangmangu east of Pondok Aren sub-district, South Tangerang City. This is indicated by the increase in the average student learning outcomes from before the best practice activities to the best practice activities at the 3rd meeting. Prior to the implementation of best practice, the average value of student learning outcomes was 84. After the best practice activities, the average value of student learning outcomes increased to 91. Direct learning model assisted by concrete models can be one of the choices of learning models for teachers who aim to controlling the content of the material and the sequence of information received by students so that students gain a full conceptual understanding of the concept of a material as well as a particular skill. ABSTRAKMatematika merupakan mata pelajaran yang dapat membangun kemampuan dan kecerdasan siswa dalam pemecahan masalah, berpikir logis, sistematis, analitis, kritis, kreatif dan solutif. Agar tujuan-tujuan pembelajaran matematika yang telah direncanakan dapat tercapai dengan baik melalui proses pembelajaran yang berlangsung di kelas, maka guru harus memilih model/metode pembelajaran, pendekatan/strategi pembelajaran, dan media pembelajaran matematika yang tepat dan disesuaikan dengan materi pembelajaran serta karakteristik siswa di kelas. Agar tercapai tujuan pembelajaran dan membantu siswa dalam memahami materi tentang pengukuran sudut, maka model pembelajaran yang digunakan untuk menyampaikan materi sudut pada siswa kelas IV SDIP Baitul Maal adalah model pembelajaran langsung dengan bantuan model konkret. Model pembelajaran langsung berbantuan media konkret dapat meningkatkan nilai hasil belajar Matematika siswa kelas IV SDIP Baitul Maal Jurangmangu timur kecamatan Pondok Aren Kota Tangerang Selatan. Hal ini ditunjukkan dengan meningkatnya rata-rata hasil belajar siswa dari sebelum dilaksanakannya kegiatan best practise sampai kegiatan best practise pertemuan ke-3. Sebelum dilaksanakannya best practice, rata-rata nilai hasil belajar siswa adalah 84. Setelah diadakannya kegiatan best practise, rata-rata nilai hasil belajar siswa meningkat menjadi 91. Model pembelajaran langsung berbantuan model konkret dapat menjadi salah satu pilihan model pembelajaran bagi guru yang bertujuan untuk mengendalikan isi materi dan urutan informasi yang diterima oleh siswa sehingga siswa mendapatkan pemahaman konsep yang penuh terhadap konsep suatu materi serta suatu keterampilan tertentu.